2002
DOI: 10.1002/cjce.5450800524
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Distribution Constants of Butane Extraction of Organic Pollutants from Aqueous Solubility

Abstract: The n‐butane/water distribution constant is one of the key parameters in determining the extraction efficiency. Experimental results on 34 organic compounds illustrated that a fundamental linear relationship exists between the distribution constant and the aqueous solubility of the solute. The relationship can be broadly applied to many different classes of chemical compounds as well as to many different solvent extraction systems. The linear equation obtained by a regression method allows one to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Correlations for butane/water and gas/butane partition coeffi cients have been constructed for 43 varied compounds. The correlation for butane/water partition coeffi cients is more general than those described before (Teo et al, 2002) because it includes a number of gaseous compounds as well as several alkanes. The correlation for gas/butane partition coeffi cients appears to be the fi rst such correlation reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Correlations for butane/water and gas/butane partition coeffi cients have been constructed for 43 varied compounds. The correlation for butane/water partition coeffi cients is more general than those described before (Teo et al, 2002) because it includes a number of gaseous compounds as well as several alkanes. The correlation for gas/butane partition coeffi cients appears to be the fi rst such correlation reported.…”
Section: Discussionmentioning
confidence: 99%
“…T he partition coeffi cients of butane extraction of organic nonelectrolytes from aqueous solution have recently been obtained (Teo et al, 2002), and useful equations have been reported that correlate the partition coeffi cients, as log Pbut, with aqueous solubilities, as log Sw with Sw in units of mmol/L or mg/L: (2), it is then possible to determine removal effi ciencies for organic nonelectrolytes from water by extraction with butane (Teo et al, 2000;Yang et al, 2004). One major diffi culty in using these equations to predict butane/water partition coeffi cient, is the requirement of determined solubilities in water.…”
Section: Randd Notementioning
confidence: 99%
See 2 more Smart Citations